Views of Port Moresby and Delena by Harry Moore Dauncey
Places or buildings include: view from the mission house, Port Moresby; view of part of the mission compound, Delena; teacher's house and garden at Dauncey's mission station, Delena. Pictures taken by/received from: Rev Harry Moore Dauncey